Rancang Bangun Alat Ukur Uji Emisi Gas Karbon Monoksida (CO) Berbasis Mikrokontroler - Sarungallo, Semuel Kete; Raka Agung, I Gusti Putu; Jasa, Lie (Jurnal Teknologi Elektro; Vol 16 No 1 (2017): (January - April) Majalah Ilmiah Teknologi Elektro, 2016)
Carbon monoxide is gas that harmful to health . Carbon monoxide is caused by motor vehicles that are not well maintened, so we need device can measure the levels of carbon monoxide. Measuring instrument created using sensor MQ - 7 based arduino uno R3 . Sensor MQ - 7 is a sensor sensitive to carbon monoxide , stable power supply 5 volts and can measure from 20-2000 ppm of carbon monoxide . Output device is data on the LCD and ISD1820 voice module , so it can be installed in an office basement .   DOI: 10.24843/MITE.1601.19
Keywords: Gas CO, Arduino Uno R3, Sensor MQ-7, ISD1820